Description of the final-instarlarva and pupa of Acanthacorydalis orientalis (McLachlan, 1899) (Megaloptera: Corydalidae) with some life history notes - Cao, Chengquan; Liu, Xingyue (Zootaxa, 2013)
The giant dobsonfly species Acanthacorydalis orientalis (McLachlan, 1899) is endemic to China and is well-known because of its remarkable large adult body size and enlarged male mandibles. However, the immature stages of this species, as well as all other Acanthacorydalis species are poorly known. In this paper we describe the last-instar larvae and pupae of A. orientalis for the first time. Aspects of the bionomics of this species is also given.